2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) 2019
DOI: 10.1109/cvpr.2019.00052
|View full text |Cite
|
Sign up to set email alerts
|

Graph-Based Global Reasoning Networks

Abstract: Globally modeling and reasoning over relations between regions can be beneficial for many computer vision tasks on both images and videos. Convolutional Neural Networks (CNNs) excel at modeling local relations by convolution operations, but they are typically inefficient at capturing global relations between distant regions and require stacking multiple convolution layers. In this work, we propose a new approach for reasoning globally in which a set of features are globally aggregated over the coordinate space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
270
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 483 publications
(288 citation statements)
references
References 28 publications
1
270
0
Order By: Relevance
“…Our ip-CSN-152, pre-trained on Sports1M outperforms I3D [3], R(2+1)D [32], and S3D-G [40] by 8.1%, 4.9%, and 4.5%, respectively. It also outperforms recent work: A 2 -Net [4] by 4.6%, Globalreasoning networks [6] by 3.1%. We note that our ip-CSN-152 achieves higher accuracy than both I3D with Non-local Networks (NL) [37] and SlowFast [10] (+1.5% and +0.3%) while being also faster (3.3x and 2x, respectively).…”
Section: Comparison With the State-of-the-artmentioning
confidence: 64%
“…Our ip-CSN-152, pre-trained on Sports1M outperforms I3D [3], R(2+1)D [32], and S3D-G [40] by 8.1%, 4.9%, and 4.5%, respectively. It also outperforms recent work: A 2 -Net [4] by 4.6%, Globalreasoning networks [6] by 3.1%. We note that our ip-CSN-152 achieves higher accuracy than both I3D with Non-local Networks (NL) [37] and SlowFast [10] (+1.5% and +0.3%) while being also faster (3.3x and 2x, respectively).…”
Section: Comparison With the State-of-the-artmentioning
confidence: 64%
“…In the above experiment, we have compared and shown that OctConv is complementary with a set of state-of-the-art CNNs [16,17,47,22,18,34,19]. In this part, we compare OctConv with MG-Conv [25], GloRe [8], Elastic [43] and bL-Net [4] which share a similar idea as our method. Seven groups of results are shown in Table 4.…”
Section: Comparing With Sotas On Imagenetmentioning
confidence: 99%
“…[15] proposed an efficient attention computation mechanism called Criss-Cross Network for semantic segmentation. [5] used the idea of bilateral filter to learn robust weighting model for object recognition. Besides, "attention" has also been proposed for image super-resolution and shown its great potential.…”
Section: Related Workmentioning
confidence: 99%